اضطرابات وظيفة الدَّرق عند النِّساء ناقصات الكثافة العظميّة بعد سنِّ الإياس (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: Low BMD is one of the most common conditions which will encounter a large population of postmenopausal women along with thyroid dysfunction. The correlation between thyroid status and BMD forms an important domain to be studied and investigated as an attempt to stop the development of osteoporosis towards its series complications. Aim: investigate the correlation between thyroid dysfunction and low BMD among postmenopausal women. Materials and Methods: This descriptive observational (case series) study was conducted on 96 postmenopausal female patients diagnosed with low BMD at Tishreen University Hospital, Lattakia, Syria, during the period between January 2018 – January 2019. Demographic data relating to age, number of menopausal years, Height and weight were analyzed. Laboratory work included thyroid status (TSH, fT3, fT4). Bone mineral density (BMD) at the lumbar spine and at the femoral neck were performed using Dual energy X-ray absorptiometry (DEXA). BMD was expressed in g/cm2 and standardized T-score/Z-score. Results: this study found a positive correlation between BMD according to Z-score and TSH values, with a statistical significant correlation relating to BMD of femoral neck p-value=0.04. A negative correlation between BMD according to Z-score and fT3 values and for lumbar spine p-value=0.01, with a statistical significant correlation relating to correlation between BMD according to Z-score and fT4 values. A statistical significant correlation between subclinical hyperthyroidism and BMD of femoral neck according to T-score with p-value=o.o2. Conclusion: There is a correlation between thyroid status and BMD, with a significant effect on BMD of femoral neck among postmenopausal women. مقدّمة: يُعدّ نقص الكثافة المعدنية العظمية أحد أشيع الحالات التي تُصادف نسبة كبيرة من النساء بعد سن الإياس؛ وكذلك الاضطرابات الدرقية، كما تشكِّل العلاقة بين الحالة الدرقية والكثافة العظمية المعدنية جانباً مهمَّاً للدراسة والاستقصاء للحدّ من تطوّر الترقق نحو اختلاطاته الخطيرة. الهدف: استقصاء الارتباط بين اضطرابات الوظيفة الدرقية ونقص الكثافة المعدنية للعظم BMD لدى النّساء بعد سن الإياس. المرضى وطرق البحث: أُجريَت هذه الدراسة الوصفية من نمط سلسلة حالات على عينة تضم 96 مريضة ناقصة الكثافة العظمية بعمر بعد سن الإياس من مراجعات مشفى تشرين الجامعي, اللاذقية, سوريا, في الفترة الممتدة ما بين شهرَي كانون الثاني 2018 وكانون الثاني 2019. تمَّ تحليل المعلومات الديموغرافية المتعلقة بالعمر والطول والوزن وعدد السنوات في سن الإياس , وشملت التحاليل المخبرية المتعلِّقة بالحالة الدرقية كل من TSH, FT3, FT4. تم قياس الكثافة المعدنية العظمية (BMD) في العمود الفقري القطني وعنق الفخذ باستخدام مقياس امتصاص الأشعة السينية مزدوج الطاقة (DEXA), والتعبير عن الكثافة المعدنية العظمية بـ (غ/سم2) و Z-score /T-score المعياري. النتائج: وجدت هذه الدراسة ارتباطاً إيجابيّاً بين قيم BMD حسب Z-score و قيم TSH مع أهميّة إحصائيّة لارتباطها بـBMD عنق الفخذ p-value=0.04. ارتباط سلبي بين قيم BMD حسب Z-score وقيم Ft3، وبالنسبة للفقرات القطنية كانتp-value=0.01. مع ارتباط إيجابي بين قيم BMD Z-score و قيم fT4.علاقة إحصائية هامّة بين فرط نشاط الدرق تحت السريري و قيم BMD لعنق الفخذ حسب T-score مع p-value=0.02. الخلاصة: إن هناك علاقة ما بين الحالة الدرقية و الكثافة المعدنية العظمية و لها تأثير هام فيما يخص عنق الفخذ عند النساء بعد سن الإياس.